2D-TDOA passive location based on geodetic longitude and latitude - Fangli MA; Yang XU; Peng XU (Tongxin xuebao)
Because of the surface of the earth is not a plane,there may be some errors in the conventional ultra-short wave passive TDOA location method using plane coordinates.In order to use the geodetic longitude and latitude coordinates directly for TDOA location,a series of spherical distance TDOA location models based on spherical two-point distance calculation were proposed.The optimal location models were adopted,and a grid point search method was applied with model validation.The numerical results show that the spherical precise calculation model has the smallest positioning error,which is independent of latitude.Positioning error of the spherical approximation calculation model is worse than the first model,and increases with the increase of latitude.The equidistant orthographic cylindrical projection model has a small positioning error in the low latitudes.However,it has a large positioning error in the middle and high latitudes.The equiangular orthographic cylindrical projection model and the equiareal orthographic cylindrical projection model have a relatively large positioning error,which is around 26% at any latitude and is not applicable.